62: EVIDENCE-BASED "PODCAST"; A QUEST TO REDUCE UNNECESSARY DEMANDS. (8th February 2017) - Mostafaei, Hadi; Hajebrahimi, Sakineh
Abstract : Background and aims: The unnecessary demands both from patients and doctors cause a great amount of financial waste and negative impact on patients' health. Thus there is a need for informing the public about the necessity of certain demands and the evidence behind them. Therefor we decided to launch a podcast channel with the aim of discussing top health issues and top demands and giving the listeners and understanding of what demands are their real need. Methods: We began recording the 20 minute podcasts discussing some of the most widespread demands. The podcasts were recorded in a studio with asking guest experts to join. These podcast were spread in public using common national social media app "Telegram" and creating a telegram channel. After two series of podcasts and sharing them in the Telegram channel, we shared a short and simple questionnaire and we asked the public to fill it up. We asked them about: Popularity of the discussed topics, their previous wrong beliefs, Usefulness of the data, the effect of the provided information on their education and impact on their habit change. The data gathered was finally analyzed. Results: From 200 members of the channel 80 members responded for our questionnaire call. All the respondents at least had primary education. Most of them spend a minimum of one hour per day using Telegram and the information derived of Telegram has a high impact in their education. The respondents were shocked when hearing the two of their most common demands were completely unnecessary. They mostly agreed that high quality, Inviting well-known experts and discussing common and relevant issues makes the Podcast more trustworthy. All known the members of the channel were unfamiliar with the importance of Evidence-Based education after listening to podcasts; they agreed not to trust any data at a glance. Most of them decided for making a habit change. This concludes the importance of Evidence-Based education and the great role of the social media in its success.